Eucalyptus spp. - Ciesla, W.M.; Diekmann, M.; Putter, C.A.J.; Food and Agriculture Organization of the United Nations (1996)
The purpose of the joint FAO/IPGRI programme is to generate a series of crop/tree-specific technical guidelines that provide relevant information on disease indexing and other procedures that will help to ensure phytosanitary safety when germplasm is moved internationally. The scope of the recommendations in these quidelines is confirmed to small, specialized consignments used in technical programmes, e.g. for conservation, research and basic plant breeding programmes. Eucalypts are the mst widely grown trees in exotic plantations worldwide. At the end of 1990, there were an estimated 10.06 million ha of eucalypt plantings in the tropics, comprising 23% of all tropical forest plantings (FAO 1993). Most of the species originate in Australia, the 'isolated continent.' Australia is rich in biodiversity and eucalypts dominate the tree cover of areas which receive in excess of 500 mm of annual precipitation. Introduction of exotic pests into Australia in the future could severely damage entire ecosystems. The catastrophic damage caused by the root pathogen Phytophthora cinnamomi to Eucalyptus marginata and other components of native vegetation in Western Australia is an example. Of particular concern are pests which do not currently occur in Australia and appear to have adapted to eucalypts.